An investigation into the use of plastic chips to reduce collapsibility in loess-like soils at Mount Moorosi Village, Lesotho - Venter, Jason (Department of Civil Engineering, 2022)
Mount Moorosi Village, located within the Senqu River Valley in Lesotho, has experienced significant damage to its buildings over the last several years, due to severe cracking. The cause of these cracks has been attributed to the local soil, which presents itself as an ideal building and founding material, while it may in fact be to the contrary. A previous investigation by Damane (2019), into the underlying soil profile of Mount Moorosi Village concluded that the village was underlain by a top layer of silty-sandy loess, a windblown soil of at least 3 m in thickness, with the majority of its grains falling within the siltsized particle range. The material demonstrated significant warping potential as well as a high hydrocollapse potential. To attempt to mitigate the hydrocollapse potential of the soil, linear low-density polyethylene (LLDPE) pellets, made from recycled plastic waste, were blended with the soil at concentrations of 3, 6 and 9 % by mass, before being subjected to pycnometer, oedometer and triaxial tests, to determine the specific gravity of the blended soil as well as the settlement and shear strength parameters, respectively. Test results showed that the addition of the LLDPE chips, at 6 % concentration by mass, resulted in the maximum improvement in both the settlement and shear strength parameters. The soil's collapse and hydrocollapse coefficients were reduced by 54 and 40 % respectively, with the overall classification of the soil going from ‘severe' to ‘moderately severe'. The cohesion of the soil was improved by 8 and 400 % for field and saturated moisture contents, respectively. The internal angle of friction of the soil was increased by 97 and 150 % for field and saturated moisture contents, respectively. Collapse and settlement calculations, conducted on Settle3D, showed that the soil's overall settlement was reduced by 34 and 54 % for field moisture and saturated soil conditions, respectively. The total settlement of the strip foundations with their current dimensions, however, was still outside of the acceptable ranges. The total settlement was lowered to within acceptable range of under 50 mm when the width of the strip footings was widened to 750 mm, and their depth increased to 200 mm.